The Geopolitical and Strategic Importance of Eurasia in Regional and International visions - شهيله, شادي (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research discusses the importance of the Eurasia region in terms of geopolitical and strategic location, and the nature of the resources and wealth it possesses, by reviewing the most important geopolitical theories that focused on the importance of Eurasia's position in controlling the world. The research found that the Eurasia region was of great importance in terms of geopolitics and strategy, and that the economic importance of Eurasia lies in the resources it possesses, in addition to being commercial transit areas and corridors for gas transmission lines from Asia towards Europe, and the interests of countries Some of them want to achieve economic goals, some want to strengthen their security capabilities, and some aspire to achieve political goals represented in standing in the face of Western hegemony, especially the United States. Keywords: World Land, Heart Land, Rimland, New Eurasian.